Assessment of aerosol optical property and radiative effect for the layer decoupling cases over the northern South China Sea during the 7‐SEAS/Dongsha Experiment. Issue 9 (12th May 2016) - Pani, Shantanu Kumar; Wang, Sheng‐Hsiang; Lin, Neng‐Huei; Tsay, Si‐Chee; Lolli, Simone; Chuang, Ming‐Tung; Lee, Chung‐Te; Chantara, Somporn; Yu, Jin‐Yi
Abstract: The aerosol radiative effect can be modulated by the vertical distribution and optical properties of aerosols, particularly when aerosol layers are decoupled. Direct aerosol radiative effects over the northern South China Sea (SCS) were assessed by incorporating an observed data set of aerosol optical properties obtained from the Seven South East Asian Studies (7‐SEAS)/Dongsha Experiment into a radiative transfer model. Aerosol optical properties for a two‐layer structure of aerosol transport were estimated. In the radiative transfer calculations, aerosol variability (i.e., diversity of source region, aerosol type, and vertical distribution) for the complex aerosol environment was also carefully quantified. The column‐integrated aerosol optical depth (AOD) at 500 nm was 0.1–0.3 for near‐surface aerosols and increased 1–5 times in presence of upper layer biomass‐burning aerosols. A case study showed the strong aerosol absorption (single‐scattering albedo ( ω ) ≈ 0.92 at 440 nm wavelength) exhibited by the upper layer when associated with predominantly biomass‐burning aerosols, and the ω (≈0.95) of near‐surface aerosols was greater than that of the upper layer aerosols because of the presence of mixed type aerosols. The presence of upper level aerosol transport could enhance the radiative efficiency at the surface (i.e., cooling) and lower atmosphere (i.e., heating) by up to −13.7 and +9.6 W m −2 per AOD, respectively. Such enhancement could potentially modify atmospheric stability, can influence atmospheric circulation, as well as the hydrological cycle over the tropical and low‐latitude marginal northern SCS. Key Points: First optical investigation of moderately absorbing upper layer biomass‐burning aerosols over northern SCS Enhanced surface cooling and free troposphere warming by the transported biomass‐burning plumes were quantified Atmospheric heating rate was estimated as high as 1.3 K d −1 for upper layer aerosols over tropical northern SCS